# Answer to Question #29454 in Functional Analysis for chantelle francis

Question #29454

3. If f(x) = 2x + 4 and g(x) = - 3. Given that h(x) = g(x) – f(x). Find h(x).

Expert's answer

Substituting we obtain

h(x) = g(x) – f(x) = - 3 - (2x + 4) = - 3 - 2x - 4 = -2x - 7.

h(x) = g(x) – f(x) = - 3 - (2x + 4) = - 3 - 2x - 4 = -2x - 7.

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment